The ancient history of the Internet. - Diamond, Edwin; Bates, Stephen (American Heritage)
Traces the history of the Internet. Development of the Internet from the analytical system devised in World War II; Operations analyses conducted by the military using calculating devices; United States' creation of an image as a technology superpower; Science and math requirements in schools and colleges to outpace the Soviets in analytical devices development; Computer network prior to Internet. INSET: ...and then there was Usenet..